Identification of Groundwater Potential Zones Using Analytic Hierarchy Process (AHP) Based on Webgis in North Central Timor District - Susu, Yublina Rambuhana; Kelen, Yoseph Pius Kurniawan; Lestari, Anastasia Kadek Dety; Gelu, Leonard Peter (Journal of Artificial Intelligence and Software Engineering, 2025)
In all kinds of human activities, water is a basic need to carry out various activities. Therefore, water is very functional and plays an important role in the life of living things on this earth. Groundwater is a very important source of water supply, especially in areas where long dry seasons or droughts cause rivers to stop flowing. Geographic information systems (GIS) can be used to help map groundwater. In this study, it was applied in determining the potential zones of groundwater availability in the area with several parameters such as rainfall, lithology, geomorphology. The entire map is then weighted using the analytical hierarchical process (AHP) method to determine the potential zones of groundwater availability, the results will be displayed and informed in the Website system. The combination of AHP and Waterfall methods shows that high water potential areas in North Central Timor Regency are in Noemuti, South Bikomi, Insana, East Noemuti, and West Miomafo Districts, moderate water potential in East Miomafo District, Kefamenanu City, Insana Fafinesu, Central Miomafo, Musi, Mutis, Biboki Feotleu, Biboki Moenleu, North Biboki, Central Bikomi, West Insana, South Biboki, and low water potential in Bikomi Nilulat, Biboki Anleu, Biboki Tanpah, and North Insana Districts.